The placenta in infants >36 weeks gestation with neonatal encephalopathy: a case control study. Issue 3 (12th July 2012) - Hayes, Breda C; Cooley, Sharon; Donnelly, Jennifer; Doherty, Elaine; Grehan, Andrea; Madigan, Cathy; McGarvey, Cliona; Mulvany, Siobhan; Ryan, Stephanie; Gillian, John; Geary, Michael P; Matthews, Tom G; et al.
Abstract : Objective: To determine placental characteristics associated with neonatal encephalopathy (NE) and correlate these with short- and long-term neurodevelopmental outcome. Design: Case/control study. Setting: Neonatal Intensive Care Unit, Rotunda Hospital, Dublin, Ireland. Patients: Newborns ≥36 weeks gestation, with NE (cases). Healthy term newborns (controls). Interventions: Placental pathology was obtained from the official placental report. Brain MRI was blindly reviewed. Children were assessed using a variety of standardised assessments. Data were analysed using multinomial logistic regression analysis. Main outcome measures: RRR for grade of encephalopathy. OR for neurodevelopmental outcome. Results: Placental reports were available on 141 cases (76 grade 1; 46 grade 2; 19 grade 3) and 309 control infants. Meconium phagocytosis, haemorrhage, raised placental to birth weight ratio and/or markers of infection/inflammation were independently associated with NE and showed a synergistic effect, when combined, for short- and long-term impairments. Conclusions: Evaluation of the mechanisms leading to the placental characteristics identified may help to characterise the causal pathway of NE.